2009
DOI: 10.1007/s00704-009-0115-z
|View full text |Cite
|
Sign up to set email alerts
|

Onset of the summer monsoon over the southern Vietnam and its predictability

Abstract: The summer monsoon onset over southern Vietnam is determined through a new criterion based on both in situ daily rainfall at 6 selected stations provided by the Institute of Meteorology and Hydrology, Vietnam, and the zonal component of the wind at 1000hPa from the National Center for Environmental Prediction/Department of Energy reanalysis 2 (NCEP/DOE-II). Over the period 1979-2004, the summer monsoon onset mean date is on 12 May, with a standard deviation of 11.6 days. The temporal and spatial structures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…The mean OD in 1979-2010 over Vietnam and the South China Sea region (7.5-25°N, 100-120°E) in this study is 10 May (standard deviation is 21 days). This is consistent with findings from several studies such as Pham et al [2010], ZW08, and Wang et al [2004] who found the mean OD over the Indochina Peninsula to be during the first weeks of May. The mean withdrawal date of the summer monsoon rainfall in Vietnam is on 21 September (standard deviation is 14 days).…”
Section: Vietnam and The South China Seasupporting
confidence: 91%
See 1 more Smart Citation
“…The mean OD in 1979-2010 over Vietnam and the South China Sea region (7.5-25°N, 100-120°E) in this study is 10 May (standard deviation is 21 days). This is consistent with findings from several studies such as Pham et al [2010], ZW08, and Wang et al [2004] who found the mean OD over the Indochina Peninsula to be during the first weeks of May. The mean withdrawal date of the summer monsoon rainfall in Vietnam is on 21 September (standard deviation is 14 days).…”
Section: Vietnam and The South China Seasupporting
confidence: 91%
“…This is consistent with findings from several studies such as Pham et al . [], ZW08, and Wang et al . [] who found the mean OD over the Indochina Peninsula to be during the first weeks of May.…”
Section: Application Of the Indexmentioning
confidence: 99%
“…It is observed that rainfall in NVN is governed by early summer TCs, northward migration of the intertropical convergence zone (ITCZ), and mesoscale convective systems. Southwesterly summer monsoon is the predominant precipitating mechanism in SVN (Pham et al 2010). CVN, however, has rainy season delayed until fall and early winter due to fall TCs, southward-migration ITCZ, and cold surges and interactions among them and topography (Yokoi and Matsumoto 2008;Yen et al 2011).…”
Section: Datamentioning
confidence: 99%
“…Omotosho (1992) used simple empirical schemes applied to upper-wind data for three stations across the West African Sahel to predict the onset and cessation of the rainy season for more than 2 months ahead. For Southern Vietnam, Pham et al (2010) also showed that robust atmospheric features of sub-regional scale are in phase with the dates of summer monsoon onset (i.e. pressure and moist static energy gradients, outgoing long-wave radiation [OLR] and wind fields).…”
Section: Introductionmentioning
confidence: 99%